Local ablation of hepatocellular carcinoma by interstitial brachytherapy: prediction of outcome by diffusion-weighted imaging. (April 2023) - Thormann, Maximilian; Surov, Alexey; Pech, Maciej; March, Christine; Hass, Peter; Damm, Robert; Omari, Jazan
Background: Interstitial brachytherapy (iBT) has become a viable treatment option in the therapy of early and intermediate stage hepatocellular carcinoma (HCC). Prognostic imaging tools to predict patient outcome are missing. Purpose: To assess the predictive value of baseline diffusion-weighted imaging in HCC before iBT with regard to local tumor control and overall survival (OS). Material and Methods: We retrospectively identified 107 patients who underwent iBT for HCC from 2011 to 2018 from our database. Apparent diffusion coefficient (ADC) values for each treated lesion were analyzed in region of interest measurements. Additionally, explorative combined ratios adjusting total measured lesion area and mean measured lesion area per patient by ADC values were calculated. Measurements underwent a univariate and multivariate Cox regression analysis. The log rank test was then used to verify prognostic cutoff levels for median survival time. Results: A total of 189 lesions in 81 patients were measured. Median survival of patients was 46.0 months. Neither ADC parameter was indicative of local tumor control. Lesion size >5 cm was associated with lower local tumor control (hazard ratio [HR]=4.292, 95% confidence interval [CI]=1.285–14.331; P  = 0.018). Average measured lesion area divided by ADCmin (ADCarea mean, min ) was identified to independently predict OS (HR=1.994, 95% CI=1.172–3.392; P  = 0.011). A cutoff based on the variable's median (0.29 × 10–4 AU) identified patients with poor outcome (OS 36 vs. 61 months) for lower ADCarea mean, min values as verified by the log-rank test ( P  = 0.040). Conclusion: Pre-treatment ADCarea mean, min may serve as an independent predictor of OS in patients with HCC undergoing iBT.